Réponses

2014-04-10T17:33:00+02:00
Développer l'expression :

A = (4x-1)² - (2x+4)(4x-1)
A= 16x² - 8x +1 - (8x² -2x +16x-4)
A= 16x² -8x +1 -8x² -14x +4
A= 8x² -22x +5
Factoriser:
A = (4x-1)² - (2x+4)(4x-1)
A= (4x-1)[(4x-1)-(2x+4)]
A= (4x-1)( 4x-1 -2x-4)
A=(4x-1) ( 2x -5)
2014-04-10T17:41:55+02:00
Développer l'expression :

A = (4x - 1)² - (2x + 4) (4x - 1)
A = 16x² - 8x + 1 - (8x² -2x +16x - 4)
A = 16x²  - 8x² - 8x + 2x - 16x + 1 + 4
A = 8x² - 22x + 5

Factoriser l'expression :
A = (4x - 1)² - (2x + 4) (4x - 1)
A =  (4x - 1) ((4x - 1) - (2x + 4))
A = (4x - 1) (4x -1 - 2x - 4)
A = (4x - 1) (2x - 5)